2010
DOI: 10.1002/ijc.25314
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal hormone therapy and breast cancer risk: Impact of different treatments. The European Prospective Investigation into Cancer and Nutrition

Abstract: Menopausal hormone therapy (MHT) is characterized by use of different constituents, regimens and routes of administration. We investigated the association between the use of different types of MHT and breast cancer risk in the EPIC cohort study. The analysis is based on data from 133,744 postmenopausal women. Approximately 133,744 postmenopausal women contributed to this analysis. Information on MHT was derived from country-specific self-administered questionnaires with a single baseline assessment. Incident b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 88 publications
8
73
0
1
Order By: Relevance
“…However, previous studies suggest that neither the type of estrogen nor the type of progestin influence the risk of breast cancer. 10,21,28 Thus, differences between the European and U.S. studies may be explained by differences in the monthly doses of progestin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous studies suggest that neither the type of estrogen nor the type of progestin influence the risk of breast cancer. 10,21,28 Thus, differences between the European and U.S. studies may be explained by differences in the monthly doses of progestin.…”
Section: Discussionmentioning
confidence: 99%
“…39 Our findings of an increased risk of breast cancer for both continuous and sequential combined preparations of EPT are in agreement with previous studies. 3,10,13,15,[19][20][21] A study showed an increased risk of breast cancer for continuous compared with sequential preparations of estradiol-NETA. 27 We found a higher RR in continuous than in sequential preparations, but the differences were not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of birth control pills in women with higher SES also affects their hormone imbalance and thus may increase the risk of breast cancer (Gierisch et al 2013;Bakken et al 2011). Some other studies have also suggested that because women with higher SES are likely to have less children or have children at later age, their risk of developing breast cancer may be modified (Ewertz et al 1990;Rosner et al 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Sequential versus continuous MHT. Recent data suggest that sequential MHT is associated with a lesser risk than combined continuous MHT ( 15 ).…”
Section: Estrogens Plus Progestogensmentioning
confidence: 99%